Analysis of The Effect Of Employee Compensation and Employee Career Development on Employee Performance at The Regional General Hospital of Ciamis District - Anton Wahyu Radityananto; Asep Kusdiman Jauhari; Sugeng Riyanto (Doctoral Program of Social Science Pasundan University, 2021)
This research starts from the fundamental problems of low performance of employees at the Ciamis District Regional General Hospital. It thought to have been coming by Employee Compensation and Employee Career Development towards Employee Performance at the Ciamis District Regional General Hospital, not yet implemented. The approach in this study refers to the context of the theory of Employee Compensation and Employee Career Development also Employee Performance as part of the scope of Public Administration. The method of research used an explanatory survey with technical analysis Structural Equation Modeling (SEM), while the population of Ciamis District General Hospital. The results of the study showed the need for further research on the optimization of the increasing influence of Employee Compensation and Employee Career Development on Employee Performance at the Ciamis District Regional General Hospital, viewed from the perspective of Public Administration. This is indicated by the existence of other variables that influence the Employee Performance at the Ciamis District Regional General Hospital.